The Effect of Once-Weekly 70 Mg Alendronate Versus Once-Daily 10 Mg Alendronate in the Treatment of Postmenopausal Osteoporosis - İlker Çorapçı; Cengiz Öner; Onur Armağan; Yavuz Selim Pehlivan; Funda Taşçıoğlu (Galenos Yayinevi, 2004)
The aim of this study was to compare the effect of once-weekly 70 mg alendronate versus once-daily 10 mg alendronate in the treatment of postmenopausal osteoporosis. Sixty-three women with postmenopausal osteoporosis were randomly assigned to two groups. The first group consisting of 26 patients received once-weekly 70 mg alendronate. Thirty-seven patients in the second group were treated with once-daily 10 mg alendronate. All received a daily supplement of 1000 mg calcium. Both treatment regimens were applied for 12 months. The effect of alendronate on bone mineral density (BMD) was investigated by dual energy x-ray absorbtiometry. Serum ALP, Ca and P levels and 24 hours urinary Ca excretion were assessed before the treatment and at the end of 12 months. Serum ALP levels decreased mildly, but in a statistically significant manner in both groups (p<0.05 in group 1, p<0.001 in group 2). There were no significant differences for the other biochemical parameters (p>0.05). At the end of the treatment once-weekly 70 mg alendronate and once-daily 10 mg alendronate produced significant increases in BMD at the lumbar spine (p<0.001), femur neck (Group 1, p<0.05; Group 2, p<0.01 ), trochanteric region (Group 1, p<0.05; Group 2, p<0.001) and at the Ward triangle (p<0.05). There were no significant differences between the groups with regard to side effects (p<0.05). This study indicates that both once-weekly and once-daily alendronate therapy were found to be similarly effective and safe in the treatment of postmenopausal osteoporosis.